Ultrasound Measurement as a Tool for in Situ Determination of Filling Degree Under Extreme Conditions - Schwieger, Wilhelm; Baser, Hasan-Hüseyin (Ammonothermal Synthesis and Crystal Growth of Nitrides, 2021)
Ammonothermal syntheses require high pressures and temperatures to realize the supercritical conditions. For this a special autoclave technology is required, which places special demands on both the material and the geometrical design. Characteristics are thick walls, high weight, opaque, narrow interior. Therefore the exact determination of initial weights and in particular filling degrees of liquids, which are liquid only under pressure, becomes difficult. In this section, we are going to compare three methods (i) pumping time measurement, (ii) determination by weighing and (iii) ultrasound for adjusting and/or determining the ammonia filling degree of ammonia in an autoclave are presented and the advantages and disadvantages of the individual methods are compared. In addition it is important to have the Ammonia amount very precise to describe the all the concentrations in the autoclave, even under the ammothermal conditions.
CRIS-Team Scopus Importer:2021-03-05